31.4k views
1 vote
H(x) = x2 + 1 k(x) = x – 2

(h + k)(2

User NelsonGon
by
4.9k points

2 Answers

2 votes

(h + k)(2) = 5

(h - k)(3) = 9

evaluate 3h(2) + 2k(3) = 17

User Nahom Tijnam
by
4.9k points
3 votes

Answer: 5

Explanation:

Given h(x) = x²+1 and k(x) = x-2

h(x)+k(x) = (x²+1)+(x-2)

h(x)+k(x) = x²+x-1

To get (h+k)(2), we will substitute x=2 into the resulting function to give

(h+k)(2) = 2²+2-1

(h+k)(2) = 6-1

(h+k)(2) = 5

User Laylah
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.